Ľudský kapitál a lokálny ekonomický rast na Slovensku - Rafaj, Oliver; Rehák, Štefan (Univerzita Pardubice, 2017)
Modern growth theories consider human capital as an important factor of economic growth. Cities play an important role in the production and concentration of human capital play. On their territories are located educational institutions such as universities or colleges that provide opportunities for economic actors to increase their education. They also create a space for the emergence and rapid spread of spill overs that spread inside and also outside of their territories. This article aims to examine the role of human capital in local economic growth in Slovak Republic. All 79 Slovak districts were examined and the observed time period was between the years of 2001 and 2015. For discovering the influence of the factor of human capital on the local economic growth a regression analysis was used. The main result is that the selected factor of human capital (represented by the growth index of inhabitants with tertiary education) had a positive and statistically significant influence on the economic growth of Slovakia’s districts (represented by the growth index of wages).
Keywords: local economic growth; human capital; spill overs; districts; cities; econometric model; B13; C21; R11